Discontinuation of the USMLE Step 2 Clinical Skills Examination: Studying the Past to Define the Future. (September 2021) - Howley, Lisa D.; Engle, Deborah L.
Abstract : The United States Medical Licensing Examination (USMLE) Step 2 Clinical Skills (CS) was discontinued in January 2021, marking a significant milestone in assessment of clinical skills. In this commentary, the authors trace the history of the Step 2 CS exam—beginning with its early roots in the 1960s up to its discontinuation in 2021. In this new era, the medical education community is replete with opportunities for advancing methodology and content associated with clinical skills assessment. The authors propose 3 main lessons gleaned from this rich history and modern evolution, which are aimed at defining a future that includes creative collaboration toward development of comprehensive, equitable, student-focused, and patient-centered clinical performance assessment. First, as it has done throughout history, the medical education community should continue to innovate, collaborate, and improve upon methods of clinical skills assessment. Second, medical educators should continue to shift to more complex and student-driven approaches of assessment, that is, assessments that provide an unstructured environment, are realistic with respect to the natural conditions, and do not limit students to lists of options or force them to take a certain path of reasoning. Third, medical educators should continue to rethink the role of assessment and ensure that all assessments, regardless of stakes or type, provide sufficient feedback for the student to identify areas of strength and weakness.